Virtual Field Trips: Alternatif Pembelajaran IPS pada Masa Pandemi Covid-19 - Moh Imron Rosidi; Ismaul Fitroh (Indonesian Journal of Social Science Education (IJSSE), 2021)
The Covid 19 pandemic has an impact on various sectors of human life, one of which is education. Therefore, the continuity of education must be considered seriously so that students continue to learn even during the Covid 19 pandemic. One of the breakthroughs for students to continue learning is by using a device connected to the internet or often referred to as online learning. In online learning through virtual field trips, teachers and students can access a variety of information, one of which is about learning material based on the values of kebo-keboan tradition in social studies learning which includes the theme 1. the beauty of togetherness, the sub-theme of cultural diversity in my nation in grade IV of elementary school. The design of the implementation of social studies learning based on the traditional values of kebo-keboan through virtual field trips is expected to make it easier for teachers to teach local culture-based learning materials to students, because the learning steps have been described clearly and systematically.